Liquid crystals in photovoltaics: a new generation of organic photovoltaics - Kumar, Manish; Kumar, Sandeep (Polymer journal, 2017)
This article presents an overview of the developments in the field of organic photovoltaics (PVs) with liquid crystals (LCs). A brief introduction to the PV and LC fields is given first, followed by application of various LCs in organic PVs. Details of LCs used in bilayer solar cells, bulk heterojunction solar cells and dye-sensitized solar cells have been given. All the liquid crystalline materials used in PVs are structured and the efficiency of solar cells is tabulated. Finally, an outlook into the future of this newly emerging, fascinating and exciting field of self-organizing supramolecular LC PV research is provided. Liquid crystals (LCs) have recently gained significant importance in organic photovoltaics (PVs). Power-conversion efficiency up to about 10% has reached in solar cells incorporating LCs. This review presents an overview of the developments in the field of organic PVs with LCs. Comprehensive details of LCs used in bilayer solar cells, bulk heterojunction solar cells and dye-sensitized solar cells have been given. An outlook into the future of this newly emerging, fascinating and exciting field of self-organizing supramolecular LC PV research is provided.